(untitled) (EU and comparative law issues and challenges series (ECLIC), 2020)
The author analyses the provisions of the European acquis communautaire on the liability of a railway undertaking for damages caused to passengers in the event of a train delay under Regulation (EC) No 1371/2007 on rail passengers’ rights and obligations. In particular, reference is made to the recent judgment of the Court of Justice of the European Union (CJEU) in Case C- 509/11 regarding the impossibility of exempting railway undertakings from paying compensation to passengers in the event of a delay caused by force majeure. This paper explores the latest European Commission Proposal of September 2017 for a recast of Regulation (EC) No 1371/2007 and the justification for the introduction of the force majeure clause in Art. 17 of Regulation (EC) No 1371/2007. The newly proposed provision would allow the railway undertaking to be exempt from the liability to pay compensation for a delay if it manages to prove that the delay was caused by severe weather conditions or major natural disasters that jeopardise the safe provision of service and which could not have been foreseen or prevented even by taking all reasonable measures. The paper analyses the provisions of the applicable national legislation, indicating the beginning of a full implementation of Regulation (EC) No 1371/2007 in the Republic of Croatia.